2017
DOI: 10.1007/s00068-017-0784-8
|View full text |Cite
|
Sign up to set email alerts
|

End cap versus no end cap in intramedullary nailing for displaced midshaft clavicle fractures: influence on implant-related irritation

Abstract: The use of an end cap after intramedullary nailing for displaced midshaft clavicle fractures did not result in lower patient-reported irritation rates. Although less minor revisions were observed, more major revisions were reported in the end cap group. Based on the results of this study, no end caps should be used after intramedullary nailing for displaced midshaft clavicle fractures. However, careful selection of simple fractures might be effective in reducing implant-related problems after intramedullary na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…63,[66][67] Intramedullary fixation may result in irritation at the entry site due to the protruding end of the nail. 46,[68][69][70] Smooth pins without locking mechanisms should not be used due to the potentially dire complication of pin migration. 71 While to date many prospective, comparative studies and randomized trials have been conducted in adults, there is minimal comparative literature in pediatric and adolescent populations for mid-shaft clavicle fractures.…”
Section: Complicationsmentioning
confidence: 99%
“…63,[66][67] Intramedullary fixation may result in irritation at the entry site due to the protruding end of the nail. 46,[68][69][70] Smooth pins without locking mechanisms should not be used due to the potentially dire complication of pin migration. 71 While to date many prospective, comparative studies and randomized trials have been conducted in adults, there is minimal comparative literature in pediatric and adolescent populations for mid-shaft clavicle fractures.…”
Section: Complicationsmentioning
confidence: 99%
“…The only difference between the two is that the Rockwood pin also has a trocar point on the machine thread end of the pin. Concerning the Titanium Elastic Nail (TEN) (Depuy Synthes, Warsaw, IN, USA or Stryker, Kalamazoo, MI, USA) the 43 studies that were incorporated in the analysis were comprised of seven level I, [25][26][27][28][29][30][31] eight level II, [32][33][34][35][36][37][38][39] eleven level III [40][41][42][43][44][45][46][47][48][49][50] and seventeen level IV [5,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] studies. Another type of fixation described was the Sonoma CRx (Arthrex, Naples, FL, USA) for which 6 studies (three level I, [67][68][69] one level II, [70...…”
Section: Resultsmentioning
confidence: 99%
“…Hong et al [ 21 ] suggested that triple ESINs could provide better support and stability at the fracture site, especially in subtrochanteric fractures. Slongo et al [ 32 ] suggested that End caps could avoid postoperative instability in the majority of pediatric patients with lower limb shaft fractures, even in heavier, older patients and those with instable fracture types. Thus, surgeons could use modified method to decrease the incidence rate of femur angulation when using the ESIN.…”
Section: Discussionmentioning
confidence: 99%